Pengaruh Celebrity Endorsement, Flash Sale, Dan Fear Of Missing Out (FOMO) Terhadap Impulsive Buying Pada Pengguna E-Commerce (Studi Kasus Pada Generasi Z Di Kecamatan Lowokwaru) - Ferdinand, Alang Ade; Hidayati, Nur; Millaningtyas, Restu (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The rapid development of e-commerce has triggered significant changes in consumer behavior, particularly among Generation Z, who are highly susceptible to various digital marketing strategies. One of the impacts of this change is an increase in impulsive purchasing tendencies influenced by digital marketing strategies such as celebrity endorsements, flash sales, and the fear of missing out (FOMO) phenomenon. This study employs a quantitative approach with an explanatory research design. A total of 105 respondents were selected using purposive sampling. Data analysis was conducted using multiple linear regression. The results indicate that celebrity endorsements and flash sales have a significant positive influence on impulsive purchasing behavior. Meanwhile, the influence of fear of missing out is negative and statistically insignificant. Among the three variables studied, celebrity endorsement emerged as the most dominant factor influencing impulsive purchasing decisions. This finding underscores the importance of celebrities in shaping perceptions and driving impulsive shopping behavior among Generation Z. Additionally, flash sales promotions should be further enhanced, and psychological aspects such as FOMO can be optimized in designing more effective promotional strategies. Keywords: Celebrity Endorsement, Flash Sale, Fear of Missing Out (FOMO), Impulsive Buying, Generasi Z, E-commerce